An Empirical Study on the Influence of Embedded Option on Interest Rate Risk Based on Fuzzy Monte Carlo Simulation - Enlin Tang; Zebin Liu (Journal of Mathematics)
With the gradual progress of interest rate marketization, China’s interest rate fluctuates more and more frequently, and the range is also growing. As a result, more and more implicit options are embedded in commercial banks’ balance sheets, which brings new challenges to commercial banks’ interest rate risk management. On the basis of identifying implicit options and theoretically analyzing the mechanism, fuzzy MCS method is used to calculate Ceff and Deff when implicit options exist, and compared with the traditional duration value and traditional convexity value when implicit options do not exist, further analyzing how implicit options affect the interest rate risk.